The Temporality of Situated Cognition - Vogel, David H. V.; Jording, Mathis; Kupke, Christian; Vogeley, Kai (Frontiers in Psychology, 2020)
Situated cognition embeds perceptions, thoughts, and behavior within the contextual framework of so-called “4E-cognition” understanding cognition to be embodied, enactive, extended, and embedded. Whereas this definition is primarily based on the spatial properties of a situation, it neglects a fundamental constituent: the cognitive situation as enduring. On a subpersonal level, situated cognition requires the integration of information processing within a minimal temporal extension generating the basic building blocks of perception and action (“micro-layer” of time). On a personal level, lived situations and experienced narratives leading to our biography can be defined by their broader temporal horizons (“macro-layer” of time). The macro-layer of time is based on and emerges from information processing on the micro-layer of time. Whereas the constraints on the micro-layer are primarily defined by the integrity of neurobiological processes within an individual cognitive system, the temporal horizons and subsequently the situational context on the macro-layer are defined by the complex affordances of a situation on a personal or interpersonal level. On both time layers, cognition can be defined as a continuous dynamic process, reflecting the transition from one situated state to another. Taken together, the events forming the delimiting horizons of these situations correspond to the temporal structure of the cognitive process along which it continuously proceeds. The dynamic driving and enabling this transition from state to state is synonymous with the inherent flow of time. Just as the layers of time, flow and structure, are inseparably connected. The integration of temporal flow and temporal structure into the continuous dynamic process constitutes the enduring situatedness of cognition. By providing everyday examples and examples from psychopathology, we highlight the benefits of understanding cognitive processes as part of enduring situations.